(untitled) (Journal of Forensic Medicine & Toxicology, 2014)
Tooth fracture is legally termed as grievous injury. Tooth fracture may manifest as a simple chip of enamel, loss of crown or complete avulsion. Hence, in cases of alleged assault with dental injuries, it is important to have a thorough examination of the teeth under a good lighting condition with proper equipment before giving opinion.